The Effect Of Workload And Work Stress On Courier Performance At PT. Lazada Elogistics Tasikmalaya - Nandila, Lisma Puput; Barlian, Barin; Risana, Dudu (CV. Utami, 2024)
The Purpose of this research is to determine and analyze Workload, Work Stress on courier Performance at PT Lazada Elogistics Tasikmalaya. The Research Method used was a survey method, and sampling was carried out using a purposive sampling technique. Primary data was obtained directly by distributing questionnaires to 120 courier PT Lazada Elogistics Tasikmalaya respondents and secondary data was obtained from literature review and the company. Data were analyzed using path analysis. The research results show that Workload was in the good category, Work Stress was in the good category, and Courier Performance was in the good category. Partially, Workload has a positive effect on Courier Performance, and work stress has a positive effect on courier performance. Workload and work stress simultaneously influence the courier performance at PT Lazada Elogistics Tasikmalaya Branch.